Teacher assistance to strengthen STEM learning based on lesson study at MTs Muhammadiyah 1 Malang - N. Nurwidodo; Sri Wahyuni; Iin Hindun (Universitas Muhammadiyah Malang, 2023)
STEM learning aims to prepare students to prepare themselves for a career based on the skills needed in the 21st century, but this is still not a concern for teachers so assistance is needed for science and mathematics teachers. This assistance is intended to strengthen teachers' understanding, skills, and attitudes towards STEM. The steps taken in this mentoring activity include (1) initiation of contacts and reports of initiation results, (2) discussions, (3) program planning and implementation, and (4) program evaluation. The results of the implementation of the mentoring steps, namely (1) an agreement was obtained that a comprehensive understanding of STEM concepts was needed, skills were needed to develop learning tools and implement STEM learning and a strong appreciation in STEM learning was needed; (2) agreed on the need for assistance in the form of strengthening STEM understanding, training in preparing lesson plans and STEM learning practices and strengthening attitudes towards STEM as a choice of learning approach that is in line with the demands of the 21st century; (3) The results of discussions related to program plans and implementation are the formulation of STEM training plans and their implementation involving teachers in the fields of Science and Mathematics; and (4) The results of discussions related to evaluation stated that the results of mentoring were evaluated in a process through observing STEM learning practices using the open-class and reflection method, while product evaluation was through learning plan portfolios and learning videos. The conclusion of this mentoring activity is the implementation of the stages of STEM learning assistance which includes initiation, discussion, plans and implementation of actions and evaluation. The mentoring process has strengthened the understanding, skills, and appreciation of science and mathematics teachers for STEM learning.